Vein Size Mismatch Increases Flap Failure in Lower Extremity Trauma Free Flap Reconstruction - Lee, Z-Hye; Alfonso, Allyson R.; Stranix, John T.; Anzai, Lavinia; Daar, David A.; Ceradini, Daniel J.; Levine, Jamie P.; Saadeh, Pierre B.; Thanik, Vishal (Journal of Reconstructive Microsurgery, 2019)
Background Venous outflow problems are the most common reasons for perioperative flap complications. Size mismatch in venous anastomoses poses a theoretical problem by promoting turbulent flow and subsequent thrombus formation. The purpose of this study was to determine if increased vein size mismatch is predictive of flap failure.Methods Retrospective review of our institutional flap registry from 1979 to 2016 identified 410 free flaps performed for reconstruction of lower extremity trauma. Patient demographics, flap characteristics, and flap outcomes were examined. Venous size mismatch was defined as a difference in size ≥ 1 mm between the recipient vein and flap vein.Results Vein size mismatch ≥ 1mm was present in 17.1% (n = 70) of patients. The majority of anastomoses were end-to-end (n = 379, 92.4%), and end-to-side anastomoses were preferentially used in the presence of vein size mismatch (p < 0.001). Major complications occurred in 119 (29%) flaps, with 35 (8.5%) partial flap losses and 34 (8.3%) total flap losses. Looking specifically at flaps with end-to-end venous anastomoses, venous size mismatch was associated with increased total flap failure (p = 0.031) and takeback for vascular compromise (p = 0.030). Recipient vein size relative to flap vein size (larger or smaller) had no effect on flap outcomes. Multivariable regression analysis controlling for age, sex, flap type, number of veins, recipient vein size, flap vein size, venous coupler use, and vein size mismatch demonstrated that flaps with ≥ 1 mm vein mismatch were predictive of total flap failure (p = 0.045; odds ratio: 2.58).Conclusion Flaps with vein size mismatch ≥ 1 mm demonstrated increased flap complication rates in the setting of end-to-end venous anastomoses. End-to-side anastomosis was preferentially used in vein size mismatch and carried a higher risk of flap failure. Our results support using veins of similar size for anastomosis whenever feasible to protect against flap complications.
Keywords: lower extremity trauma; venous anastomosis; vein size mismatch